Experimental voltammetry analyzed using artificial intelligence: thermodynamics and kinetics of the dissociation of acetic acid in aqueous solution - Chen, H; Li, D; Kätelhön, E; Miao, R; Compton, RG (American Chemical Society, 2022)
Artificial intelligence (AI) is used to quantitatively analyze the voltammetry of the reduction of acetic acid in aqueous solution generating thermodynamic and kinetic data. Specifically, the variation of the steady-state current for the reduction of protons at a platinum microelectrode as a function of the bulk concentration of acetic acid is recorded and analyzed giving data in close agreement with independent measurements, provided the AI is trained with accurate and precise knowledge of diffusion coefficients of acetic acid, acetate ions, and H+.